2008
DOI: 10.1227/01.neu.0000317394.14303.99
|View full text |Cite
|
Sign up to set email alerts
|

Fiducial Versus Nonfiducial Neuronavigation Registration Assessment and Considerations of Accuracy

Abstract: For our sample of 30 patients, all three registration methods provided comparable distances to the target tissue for surgical procedures. Users may safely choose anatomic registration as a less costly and more time-efficient registration method for frameless stereotaxy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 19 publications
4
37
0
2
Order By: Relevance
“…In IGS of the lateral skull base, rigid fixed marker registration with bone screws is still considered the gold-standard registration method [19]. In our study, we confirmed the high accuracy (0.33 AE 0.26 mm) of this registration method; however, its high invasiveness has prevented IGS from becoming a routine procedure in skull base surgery.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In IGS of the lateral skull base, rigid fixed marker registration with bone screws is still considered the gold-standard registration method [19]. In our study, we confirmed the high accuracy (0.33 AE 0.26 mm) of this registration method; however, its high invasiveness has prevented IGS from becoming a routine procedure in skull base surgery.…”
Section: Discussionsupporting
confidence: 78%
“…The highest accuracy values are generally obtained with registration methods that use implanted bone screw fiducials [19,20]. This minimizes the risk of registration markers being displaced between the CT imaging session and the registration process [21], which can easily occur with soft tissue-mounted adhesive fiducials [22].…”
Section: Fixed Marker Registrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been shown that accuracy decreases as the length of surgery increases due to a number of surgical, biological and technical factors related to the patient, the tools used, and environmental changes (Stieglitz, et al 2013), (Golfinos, et al 1995), (Germano, et al 1999). 4.9 ± 1.1 (Sipos, et al 1996) FARO Surgicom 2.7 (Pfisterer, et al 2008) Stealth Station (Medtronic) 4.0 ± 1.7 (Sipos, et al 1996) FARO Surgicom 2.8 (Pfisterer, et al 2008) Stealth Station (Medtronic) 3.5 ± 1.1 (Gumprecht, Widenka and Lumenta 2002) BrainLab VectorVision 4 ± 1.4 (Pillai, Sammet and Ammirati 2008) Stryker Navigation 0.91 ± 0.28 (Thompson, et al 2011) Stealth Station (Medtronic)…”
Section: Previous Work In Igns Error Analysismentioning
confidence: 99%
“…A conduta cirúrgica para pacientes com tumores cerebrais, particularmente os gliomas permanece controversa e desafiadora. O acesso com exatidão a estes tumores envolve o conhecimento anatômico e funcional apropriado diante das restrições a lesão tecidual de estruturas anatômicas eloquentes adjacente à neoplasia (Pfisterer et al, 2008;Brown et al, 1979). Tecnologia de representação gráfica moderna traz informações pré-cirúrgicas para o cirurgião evitando intercorrências.…”
Section: Cirurgia De Tumores Cerebrais Guiada Por Imagensunclassified